Expanding Pharmacy Services With an Intern Program at an Academic Medical Center. (February 2022) - Li, Hanlin; Powell, Vickie; Tsapepas, Demetra
Background: Organizations that implement pharmacy services to provide patient education have reduced hospital readmissions and improved the patient experience. The term "pharmacy extender" has been used to describe pharmacy technicians and pharmacy students who alleviate the workload of a pharmacist, enhance pharmacy visibility throughout an organization, and foster professional development for the individual. Objective: The objective of this pharmacy intern-driven program is to increase pharmacy reach for medication teaching. Methods: This is a single-center, IRB-approved retrospective cohort analysis. Pharmacist-led medication teaching is currently available to select high-risk populations including solid organ transplant and bone marrow transplant recipients at our organization. Clinicians working in the pharmacy satellites have structured operational and distributional workflow responsibilities, which precludes them from directly engaging with patients. Pharmacy interns can serve as extenders that can participate in medication teaching. An internally created digital medication teaching tool will be employed to expand the pharmacy reach for medication education. Results: During the period of study, the pharmacy interns screened 3, 993 patients and educated 2, 868 patients. Two-thirds of the pharmacy interns that participated in the program pursued post-graduate residency or fellowship training, while the rest assumed hospital pharmacist positions. Conclusion: Deploying pharmacy interns as extenders for distribution of an internally created digital tool that provides general medication teaching has shown positive outcomes including greater pharmacy presence and visibility, better patient experience, and higher patient satisfaction. Continuous data collection and monitoring are warranted to demonstrate the benefits of the program once sustained and potentially justify more resources for further expansion.